Engineering Geology for Society and Territory - Volume 8 : Preservation of Cultural Heritage - Lollino, Giorgio; Giordan, Daniele; Marunteanu, Cristian; Christaras, Basiles; Yoshinori, Iwasaki; Margottini, Claudio (Springer International Publishing : Imprint: Springer, 2015)
This book is one out of 8 IAEG XII Congress volumes, and deals with the preservation of cultural heritage. In 1972, the World Heritage Convention linked in a single framework the concepts of nature conservation and the preservation of cultural sites. Since then, engineering geology is enlarging its contributions to national and international projects on this topic and is extending its interests to key issues like: safeguarding of monuments and sites from geotechnical perspectives; advanced monitoring; investigations on cultural landscapes; development of geo-databases for cultural heritage classification; studies on the interactions between humankind, natural landscape evolution, and cultural heritage; analysis of weathering and deterioration of rock properties of monuments; risk analysis of sites affected by natural hazards; and many others. With the contributions in this book, engineering geologists, conservation scientists, and further experts from other natural, social, and economic sciences, as well as representatives of international organizations and national and local administrative authorities exchange their ideas and practices on culture heritage preservation by presenting both local case studies and multidisciplinary international projects. The Engineering Geology for Society and Territory volumes of the IAEG XII Congress held in Torino from September 15-19, 2014, analyze the dynamic role of engineering geology in our changing world and build on the four main themes of the congress: Environment, processes, issues, and approaches. The congress topics and subject areas of the 8 IAEG XII Congress volumes are: Climate Change and Engineering Geology Landslide Processes River Basins, Reservoir Sedimentation and Water Resources Marine and Coastal Processes Urban Geology, Sustainable Planning and Landscape Exploitation Applied Geology for Major Engineering Projects Education, Professional Ethics and Public Recognition of Engineering Geology Preservation of Cultural Heritage.